Pitfalls of determining the elastic properties of stabilized zirconia with indentation methods - Werbach, K.; Hummel, S.; Ebner, C.; Lohbauer, Ulrich; Peterlik, H. (Ceramics International, 2019)
Indentation methods have become popular for determining Young's modulus of materials. Though for most materials this method has been successfully applied, significant errors in the results can occur if materials respond unfavorably to standard indentation parameters. This paper presents an investigation of the effects of microindentation on yttria-stabilized zirconia compared to bulk properties obtained from resonant ultrasound spectroscopy. We not only observed different results for each method, but also a significant change of Young's modulus with indentation depth. Analysis of the microhardness indents with Raman spectroscopy revealed an indentation-induced tetragonal to monoclinic phase transformation in the material. This example shows that it is important to consider the effect of high stresses in indentation methods, as they could severely influence the determination of the material's parameters.
CRIS-Team WoS Importer:2019-04-23